Synthesis and study of structural and electrophysical characteristics of piezoceramic section (1–x)(0.8PbMgNbOBiScO3)⋅ x(0.8PbTiOBiScO3) of the ternary system BiScO3–PbTiO3–PbMgNbO3 - Artur Nogai; Maxim Sysoev; Alexandr Bush; Adolf Nogai (Journal of Advanced Dielectrics)
X-ray diffraction and dielectric studies were performed on synthesized ceramic samples of the section (1–x) (0.8PbMg[Formula: see text]Nb[Formula: see text]O[Formula: see text]BiScO3)⋅ x(0.8PbTiO[Formula: see text]BiScO3) with [Formula: see text]–1 of the ternary BiScO3–PbTiO3–PbMg[Formula: see text]Nb[Formula: see text]O3 (BS–PT–PMN) system, including the temperature dependence of thermally stimulated depolarization currents (TSDC). It was found that the samples are solid solutions with a perovskite structure, which have cubic symmetry in the range of x = 0–0.587 and tetragonal symmetry in the range of x = 0.680–1. In the intermediate composition range of x = 0.587–0.680 (morphotropic region — MR), the samples consist of a mixture of solid solutions of different symmetries. Data on the change in dielectric properties and TSDC(T) dependencies of solid solutions with a change in their composition were obtained. It was found that samples of compositions x =0–0.625 and 0.6875–1 exhibit relaxor-ferroelectric and conventional ferroelectric properties, respectively, while samples of compositions x = 0.625–0.6875 combine ferroelectric and relaxor-ferroelectric properties.